Muffin but murder - Hamilton, Victoria, 1957- (Hamilton, Victoria, 1957- Merry muffin mysteries., 2014)
Merry's career as a New York City stylist has crumbled, but her passion for muffins has helped her rise upstate in Autumn Vale. Everyone in town loves the tasty treats. Still, she would like to return to her glamorous life. Besides, the upkeep of Wynter Castle is expensive. In order to bring some prospective buyers into the mix, Merry whisks together a spooky soiree and decorates the castle with dashes of fabric and a sprinkling of spider webs. But as the revelers empty out, Merry notices one partygoer who isn't leaving -- or breathing. Now Merry must hurry to unmask a killer before her perfect plans turn into a recipe for disaster.